IMPLEMENTASI WEB GOVERNMENT SEBAGI MEDIA INFORMASI POTENSI DESA SUKARAJA - Sri Hartati; Ricky Wijaya (LPPM STMIK Pringsewu, 2016)
AbstractThe development of information technology is so rapid that one of them is the Internet can be utilized in all aspects of human life both in terms of jobs and search for information is through web-based service that is often called the website. E-government On Talbot Village is one website created to provide services and information to the public about the overall portfolio of the Talbot Village, the potentials at Talbot Village, governance structure in Talbot Village and all relevant information in Talbot Village. Development of the system is done based approach method System Development Life Cycle (SDLC) that includes the stages of planning, analysis, coding, and implementation of the system, a tool in the system development process using DAD (Data Flow Diagrams), DFD (Data Flow Diagram), and flowchart , In making this website the researchers used programming language HTML (Hypertext Markup Language), PHP (Hypertext Processor), CSS (Cascading Style sheet), JQUERY, JAVASCRIPT and presenting data in the form of MySQL. With the E-Government On Talbot Village aims to provide benefits to the wider community of the village by way of obtaining information easily, quickly, effectively and efficiently without knowing the time anytime and anywhere